Possibilities of Therapy for Hemorrhagic Shock in Patients with Gastrointestinal Bleeding - I. S. Simutis; G. A. Boyarinov; A. S. Mukhin; D. B. Prilukov (Общая реаниматология, 2014)
Objective: to evaluate the antihypoxic effect of Mexicor in patients with gastrointestinal bleeding of ulcerative etiology. Materials and methods. The paper presents the materials obtained during the treatment of 53 patients with nonvaricose gastrointestinal bleeding who were hospitalized with grades II—III hemorrhagic shock. Results. Incorporation of Mexicor into the comprehensive program for the intensive therapy of acute gastrointestinal bleeding was ascertained to reduce the activity of prooxidant processes, and the manifestations of tissue hypoxia and systemic inflammation and to improve systemic hemodynamic parameters and the clinical course of an early posthemorrhagic period. Conclusion. The use of Mexicor in patients with gastric bleeding reduces the number of complications and the duration of treatment in the intensive care unit.